A produção de texto no ensino fundamental: uma experiência pedagógica - Shimith, Regileni [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
From a diagnostic on the learning of written text, this research aimed to carry out educational activities aimed at textual production, performing operation and activity of reflection on texts written by students in a learning situation of parallel recovery, aiming to improve the standard textuality of his written production. These actions were guided from the conception of language as social practice and discourse and, later, a survey was made in the standard of textuality textual productions resulting from such actions. 5 students participated in the research of a 4th grade of elementary school, a School of Duartina peripheral zone integrating the local school system of that city. The textual productions written by these students were analyzed from three categories: common mistakes in the process of literacy, with subdivisions: phonetic transcription, dialetação, hollow hipossegmentação or vocabulary, or improper separation hiperssegmentação, overcorrection, exchange, omission or addition letters, phonemes homorganic exchange; factors textual and contextual, in which it reviewed the following factors: coherence, cohesion and story elements, clarity, in which category were analyzed: the segmentation of text into paragraphs, grammar errors of different nature, use of direct and indirect speech. The results of the intervention and ongoing analysis of data shows that there has been considered developments in the performance of the written production of the research subjects

A partir de um diagnóstico feito sobre a aprendizagem do texto escrito, esta pesquisa objetivou realizar ações educativas voltadas para a produção textual, realizando atividade de reflexão e operação sobre textos escritos por alunos em situação de aprendizagem de recuperação paralela, com vistas a melhorar o padrão de textualidade de suas produções escritas. Essas ações foram orientadas a partir da concepção de linguagem como prática social e discursiva e, posteriormente, foi feita uma sondagem no padrão de textualidade das produções textuais decorrentes dessas ações. Participaram da pesquisa 5 alunos de uma 4ª série, do Ensino Fundamental, de uma Escola da zona periférica de Duartina que integra o sistema de Ensino Municipal dessa cidade. As produções textuais escritas por esses alunos foram analisadas a partir de três categorias: “erros comuns no processo de alfabetização”, com as subdivisões: transcrição fonética, dialetação, juntura vocabular ou hipossegmentação, separação indevida ou hiperssegmentação, hipercorreção, troca, omissão ou acréscimo de letras, troca de fonemas homorgânicos; “fatores textuais” e contextuais, na qual foram analisadas os seguintes fatores: coerência, coesão e elementos da narrativa; clareza, em cuja categoria foram analisados: a segmentação do texto em parágrafos, erros de gramática de diferentes natureza, uso do discurso direto e indireto. Os resultados da intervenção feita e da análise dos dados apontam que se verificou pequenas nuances na evolução no desempenho da produção escrita dos sujeitos da pesquisa
Keywords: Linguagem; Gêneros literários; Textos; Language; Text; Textual genres; Production of written texts